2022
DOI: 10.3389/fgene.2022.982222
|View full text |Cite
|
Sign up to set email alerts
|

Roles and regulation of histone acetylation in hepatocellular carcinoma

Abstract: Hepatocellular Carcinoma (HCC) is the most frequent malignant tumor of the liver, but its prognosis is poor. Histone acetylation is an important epigenetic regulatory mode that modulates chromatin structure and transcriptional status to control gene expression in eukaryotic cells. Generally, histone acetylation and deacetylation processes are controlled by the opposing activities of histone acetyltransferases (HATs) and histone deacetylases (HDACs). Dysregulation of histone modification is reported to drive ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 140 publications
1
5
0
Order By: Relevance
“…In addition, dysregulated activation of HDAC, the major epigenetic mediator of histone modification, is known to be pro-tumourigenic and many studies have reported the use of HDAC inhibitors against HCC. 35 Here, we showed that valeric acid markedly constrains hepatic HDAC activity of NAFLD-HCC mice, consistent with a study reporting that valeric acid could act as HDAC inhibitor against hepatocarcinogenesis. 19 …”
Section: Discussionsupporting
confidence: 91%
“…In addition, dysregulated activation of HDAC, the major epigenetic mediator of histone modification, is known to be pro-tumourigenic and many studies have reported the use of HDAC inhibitors against HCC. 35 Here, we showed that valeric acid markedly constrains hepatic HDAC activity of NAFLD-HCC mice, consistent with a study reporting that valeric acid could act as HDAC inhibitor against hepatocarcinogenesis. 19 …”
Section: Discussionsupporting
confidence: 91%
“…Histone deacetylases (HDACs) reduce the activity of the target gene by removing the acetylase from the lysine residue on the histone and restoring the positive charge of the lysine. 70 HBx protein is also closely related to HDACs activities, HBV induced higher activity of HDAC1 in HCC tissue than adjacent tissue in HBV-related HCC. 71 Studies found that HBx-suppress ESR1 transcriptional activity by HDAC1, and additional Trichostatin A administration could restore ESR1 transcriptional activity.…”
Section: Aberrant Expression Of Erα In Hbv-related Diseasementioning
confidence: 99%
“…But whether HBx directly recruits DNMTs to the promoter of ESR1 is unclear. Histone deacetylases (HDACs) reduce the activity of the target gene by removing the acetylase from the lysine residue on the histone and restoring the positive charge of the lysine 70 . HBx protein is also closely related to HDACs activities, HBV induced higher activity of HDAC1 in HCC tissue than adjacent tissue in HBV‐related HCC 71 .…”
Section: Role Of Estrogen and Estrogen Receptor In Hbv Infection And ...mentioning
confidence: 99%
“…Acetylation modi cation was rstly found in histone proteins [21]. With the development of mass spectrometry technology, reversible acetylation modi cation was also found in non-histone proteins and is widely involved in many different cellular processes, such as transcriptional regulation [22][23][24][25], DNAprotein interaction [26,27], subcellular localization [28,29], cell processes [30], cell division and protein folding [31], and DNA damage repair [32,33]. In addition, non-histone acetylation modi cation can also affect protein function by regulating protein stability [34].…”
Section: Introductionmentioning
confidence: 99%